Labor productivity in Brazil during the 1990s - Régis Bonelli (Institute for Applied Economic Research (ipea), 2015)
The Brazilian economy was characterized in the 1990s by marked changes from previous decades, many of which induced by economic policy: trade and financial liberalization, privatization, other State reform measures and the beginnings of economic stabilization with the implementation of the Real Plan in the 1990s. Although Gross Domestic Product (GDP) growth rates for the decade as a whole have been below long-term averages, several indicators of macroeconomic and microeconomic performance turned for the better, especially between 1992 and 1997-1998. But few were so well succeeded as productivity change, both in the aggregate and at the sector level. This paper explores the general issue of labor productivity growth in Brazil in the 1990s following a series of steps: first, adopting a long term view, by examining to what extent overall labor productivity in the 1990s progressed at rates different from those attained in all decades since the 1940s; second, by investigating productivity growth in the manufacturing industry in the long term as well; third, by concentrating the analysis on the 1990s to cover all sectors in the economy, not just the manufacturing industries; fourth, by exploring the issue of who benefited from productivity growth in the past decade; fifth, by evaluating the role of trade liberalization and rising import penetration and its association with productivity increases. In interpreting the data assembled for the research I find that some theoretical ideas and hypothesis are not fully confirmed by the empirical results. The many qualifications and conclusions allow us to reach a better understanding of the causes and effects of productivity change in Brazil during the 1990s.
Keywords: 330